Assessment of farmers' perceptions of production constraints, and their trait preferences of sorghum in western Ethiopia: implications for anthracnose resistance breeding. (3rd April 2019) - Mengistu, Girma; Shimelis, Hussein; Laing, Mark; Lule, Dagnachew
ABSTRACT: Sorghum, Sorghum bicolor (L.) Moench is an important food security crop widely grown by smallholder farmers in sub-Saharan Africa (SSA), including Ethiopia. In SSA, the potential of sorghum production and productivity has not been realised due to an array of constraints. Colletotrichum sublineolum disease is one of the main biotic constraints causing significant yield losses. The objectives of this study were to assess farmers' perception, preferences and constraints to sorghum production and productivity in western Ethiopia, and to identify key drivers for anthracnose resistance breeding. A participatory rural appraisal study was undertaken in six selected districts in the East Wellega and West Shewa Administrative Zones in Ethiopia. Data were collected through structured questionnaires involving 165 respondent farmers. Further focus group discussions were held with 180 farmers and development agents. Sorghum is the third most preferred cereal crop after Eragrostis tef and Zea mays in western Ethiopia. About 79% of interviewed farmers cultivated sorghum during the study season. Farmers perceived that sorghum production is constrained by anthracnose disease, bird attack, loose smut and covered smut diseases. The most important farmer-preferred traits in sorghum varieties in the study areas were anthracnose resistance and tolerance to bird attack. Breeding sorghum varieties with the farmer-preferred traits is an important consideration to enhance productivity and adoption of improved sorghum cultivars in western Ethiopia.